Cross-Border Cooperation Programme As an Impetus for Establishment of New Modes of Governance in Croatia - Marijana Sumpor; Irena Dokic; Jaksa Puljiz (European Regional Science Association (ERSA), 2006)
Generated as a response to the requirements in managing European cross border cooperation programmes, Neighbourhood Programme Slovenia-Hungary-Croatia 2004-2006 (NP) in particular served as an impetus for establishment of new modes of governance in Croatia. Together with Hungary and Slovenia, Croatia participates in this trilateral Programme as an external EU border candidate state. The NP is implemented as a grant scheme in Croatia for the first time requiring many institutional changes for its implementation. On all levels of government, the NP contributed to the establishment of stronger relations among institutions, horizontally and vertically, and a transfer of know-how in preparation and implementation from experienced partners, Slovenia and Hungary. Such a complex programme generated also problems due to weak administrative capacity, different sources of financing and socio-economic discrepancies. On national level, weak capacity of the Croatian Ministry of Foreign Affairs and European Integration (MFAEI) has directly influenced the initiation and implementation of NP and difficulties in the decision-making process occurred. The relationship between MFAEI and the Delegation of the European Commission was unclear and there were difficulties in developing new administrative procedures. Additionally, insufficiently transparent information dissemination mechanisms through different government levels influenced the quality and selection of project proposals in certain counties. Socio-cultural differences in Croatia were insufficiently considered while setting up the coordination system resulting in the extent and quality of submitted proposals and their success in the selection procedure. Some regions showed successful coordination on county level contributing to selection of greater number of proposals from those counties, while in others, there was a lack of capacity in preparing coherent project proposals. In accordance with the presented first Croatian experiences in the trilateral European cross-border programme, the following can be concluded: In terms of socio-developmental impacts, the joint-project proposal preparation process of the cross border partners created intensive inter-institutional cooperation and inter-institutional communication. However, only successful project proposals result in inter-institutional collaboration through joint implementation of projects, which is considered fundamental to the creation of a network society and building of social capital.
Keywords: 330